Synthesis of Low Dimensional Carbon Nanostructures for Sensing, Bio-imaging and Optoelectronic Devices - Alam, Md Bayazeed (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Synthesis of Low Dimensional Carbon Nanostructures; Sensing, Bio-imaging; Optoelectronic Devices